Synthesis of structured lipid 1, 3-dioleoyl-2-palmitoylglycerol in both solvent and solvent-free system. Issue 2 (March 2015) - Wei, Wei; Feng, Yongfang; Zhang, Xi; Cao, Xi; Feng, Fengqin
Abstract: To obtain high purity of 1, 3-Dioleoyl-2-palmitoylglycerol (OPO), an important structured triglyceride for infant formula, a facile method was established. Tripalmitin (PPP) was firstly synthesized, and then OA was incorporated into the sn -1 and 3 position of the PPP glycerol backbone by acidolysis catalyzed using sn -1, 3 regiospecific lipases. Two kinds of widely used immobilized sn -1, 3 regiospecific lipases, Lipozyme TL IM and Lipozyme RM IM, were investigated in both solvent ( n -hexane) and solvent-free system. The results showed that Lipozyme TL IM and Lipozyme RM IM were suitable for solvent system and solvent-free system respectively. Other reaction conditions (enzyme load, substrate molar ratio, temperature, reaction time) were optimized. The palmitic acid (PA) at the sn -2 position of the obtained triacylglycerols (TAGs) under optimized conditions were 92.92% and 86.62%, and OPO contents in the final products were 32.34% and 40.23% in the solvent and solvent-free system respectively. Special emphasis was given to test the reusability of the two immobilized lipases, results showed that Lipozyme TL IM was almost non-reusable, while Lipozyme RM IM could keep its activity for at least 15 times (about 60 h). These results provide a guide for the industrial production of high purity OPO by facile method. Highlights: Facile methods for synthesis of high purity OPO have been established. Lipozyme TL IM and Lipozyme RM IM have different performances in solvent and solvent-free system. In acidolysis reaction, Lipozyme RM IM could be reused at least 15 times. In acidolysis reaction, Lipozyme TL IM was almost disposable.